Clinicopathological features of colorectal polyps: evaluation of the 'predict, resect and discard' strategies. (24th June 2013) - Sakamoto, T.; Matsuda, T.; Nakajima, T.; Saito, Y.
Abstract Aim 'Predict, resect and discard' strategies for diminutive and small colonic polyps are considered to be cost effective for treating colorectal cancers. The aim of this study was to determine, retrospectively, the histological features of colonic polyps resected by endoscopic procedures or surgery using an updated database. Method We retrospectively analysed the clinicopathological features of colorectal polyps, less than 20 mm in size, which were removed by endoscopy from January 2009 to November 2011 at the National Cancer Center Hospital (NCCH) in Tokyo, Japan. Results Less than 1% of diminutive polyps (≤ 5 mm) were classified as mucosal high‐grade neoplasia (Category 4), and no submucosal invasion by carcinoma (Category 5) lesions were noted. However, 3% of small polyps (6–9 mm) were classified as Category 5; of these, 6% were submucosal deep invasive cancers. Morphologically, depressed components were observed more frequently in carcinomas than in adenomas in both small and large polyps (10–20 mm). Conclusion In light of the 'predict, resect and discard' strategies for small polyps, we should pay attention to the possible clinical malignancy of small and large polyps. We recommend that these strategies should be applied selectively and that they should be informed by accurate endoscopic evaluations.